Vigs: Implikasies vir Suid-Afrikaanse verpleegkundiges - Deel 1 - Michael C Herbst (AOSIS, 1985)
At present the number of AIDS victims in South Africa has been small with only 19 cases reported by 19 July 1985. Nurses in South Africa should however understand AIDS (Auto Immune Deficiency Syndrome) so that a possible sudden increase in the number of cases does not Find them unprepared. AIDS is a disease characterised by the development of an inexplicable immune deficiency. These patients develop fatal opportunistic infections and a specific malignancy - Kaposi Sarcoma. AIDS is believed to be caused by a retro-virus named HTLV-III. It seems to be spread through sexual contact, blood, blood products, syringes of drug-addicts and to a baby during the birth process. The diagnosis of AIDS is made on the basis of an opportunistic infection or the development of a malignancy. Four patterns have been identified including the pulmonary, central nervous system, gastro-intestinal and fever o f unknown origin patterns. (Next issue: Nursing patients with AIDS).